Burnout, Penurunan Kualitas Interaksi, Mutasi dan Resignasi Pada Sekolah Islam: Kajian Workload dalam Manajemen Sumber Daya Manusia - Anniez Rachmawati Musslifah; Faqih Purnomosidi; Dhian Riskiana Putri; Erna Indriastiningsih (Program Studi Teknik Industri Universitas Setia Budi, 2025)
The increasing workload on teaching and administrative staff in Islamic boarding schools has become a crucial issue in human resource management (HR) practices. This study aims to analyze workload distribution, identify influencing factors, and evaluate its impact on overall staff performance. The study employed a qualitative approach through fieldwork, with the research location being an Islamic boarding school in Central Java, purposively selected based on its operational complexity and high academic and non-academic activities. Data collection techniques included in-depth interviews with 15 participants (teachers, administrative staff, and management), participant observation, and analysis of the school's internal policy documents. The results revealed an inequitable distribution of workload across departments. Boarding school teachers, for example, juggles administrative duties and student guidance without adequate compensation or regulation. Nine of the 15 participants reported experiencing emotional exhaustion, loss of work motivation, and exhibiting clear symptoms of burnout. Five of them expressed a desire to transfer or resign. This situation was exacerbated by a lack of standardized tasks, the high demands of 24-hour work in the boarding school environment, and the pressures of an integrated curriculum. Burnout also impacts the quality of interactions between staff and decreases teacher engagement in learning activities. This study recommends the development of job analysis-based work guidelines, enhanced psychological support, time management training, and technology integration to optimize the workload management system sustainably.